Optimalization of Green Sukuk as an Effort to Develop Sustainable Development (SDGs) in Review of Maqashid Sharia - Ayu Alifia, Putri Ismukhanah; Fakhriah, Nayli (Majapahit Journal of Islamic Finance and Management, 2024)
Rapid economic development contributes to environmental sustainability. Some of the negative impacts caused by irresponsible economic activity are air pollution, water pollution, and damage to biodiversity, which ultimately contribute to climate change. This study aims to determine the role of green sukuk in sustainable development efforts in the Maqasid Sharia review. Green Sukuk is an innovative financial instrument based on Sharia principles to support Indonesia's commitment to address climate change. Awareness of the sustainability of nature is the basis for environmentally sound development. This research uses descriptive qualitative research methods with data collection techniques, namely literature and research studies obtained from scientific journals, scientific articles, books, and research reports that contain information on green sukuk, sustainable development, Sustainable Development Goals (SDGs), and Maqasid Sharia. The results of this study explain that the integration of green sukuk in sustainable development efforts is in line with Maqasid Sharia, which aims to provide benefits for the community. There are still relatively few studies that discuss the Maqasid Sharia perspective about green sukuk. Thus, this study contributes to the literature on Islamic finance and sustainable development by offering a new perspective on the potential of green sukuk in supporting SDGs and addressing the challenges of climate change in accordance with Sharia principles.